Prevalence of respiratory symptoms among female workers in the fish processing industry in Odisha - Ghosh, Tirthankar; Patel, Jigisha (International Journal of Occupational Safety and Health, 2024)
Introduction: The fish processing industry has shown a major scale of growth in recent years. The aim of the present study was to assess the respiratory and pulmonary problems of the female workers of the fish processing industry. Methods: A total of 60 female workers out of which 40 were in pre processing unit and 20 were in post processing unit of fish processing work were selected randomly for the study held in a fish processing factory in Patia, Odisha, India. The study involved the assessment of physical parameters, application of a questionnaire based on respiratory and pulmonary issues, spirometry for monitoring lung function and Peak expiratory flow rate (PEFR). The study also included an assessment of the worksite by OSHA – recommended ergonomics checklist. Results: The fish processing workers were found to complain about respiratory symptoms. Continuous exposure to the fish processing environment leads to a significant reduction in peak expiratory flow rates and lung volumes respectively. The study indicated that female fish processing workers have respiratory and pulmonary problems which might be due to prolonged exposure to the low ambient temperature, cold air loaded with bioaerosols and allergens, and direct contact with chlorinated cold water in their respective work environment. Conclusion: The fish processing workers were found to complain about respiratory discomfort in the workplace. Prolonged exposure to cold fish processing environments may lead to acute and chronic respiratory disorders.